What Can (Or Should) Linguists Do in The Face of Language Decline? - Edwards, John (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1994)
In a recent exchange in Language, Michael Krauss and Peter Ladefoged differed over the role of linguists in the face of language decline. Krauss argued that the discipline must not “preside obliviously” over the disappearance of nine-tenths of its field; Ladefoged advocated a more traditional and detached stance, and suggested that linguists ought not to assume that they know best. What are the central issues informing this matter? What facts are relevant to a choice between active involvement and dispassionate study? This paper will discuss some of the recurring elements in situations of language decline. These elements are remarkably constant, and it is in their particular combinations that the uniqueness of different contexts resides. Based upon this, it is suggested that the necessary will to stanch decline is a tenuous quality. Beyond this, the paper will comment upon the ahistorical manner in which modern settings of language decline are treated, and upon the larger language-group identity relationship which is often the heart of the matter. The paper concludes by proposing that a middle ground between the Krauss and Ladefoged positions is appropriate and that there are, in fact, ways for linguists (and others) to become “involved” without sacrificing disinterested scholarship. We need not, after all, surrender the field to what Dwight Bolinger once called the shamans of language.